Heterotrimeric G protein signaling via GIV/Girdin: Breaking the rules of engagement, space, and time. (16th February 2016) - Aznar, Nicolas; Kalogriopoulos, Nicholas; Midde, Krishna K.; Ghosh, Pradipta
Abstract : Canonical signal transduction via heterotrimeric G proteins is spatially and temporally restricted, that is, triggered exclusively at the plasma membrane (PM), only by agonist activation of G protein‐coupled receptors (GPCRs) via a process that completes within a few hundred milliseconds. Recently, a rapidly emerging paradigm has revealed a non‐canonical pathway for activation of heterotrimeric G proteins by the non‐receptor guanidine‐nucleotide exchange factor (GEF), GIV/Girdin. This pathway has distinctive temporal and spatial features and an unusual profile of receptor engagement: diverse classes of receptors, not just GPCRs can engage with GIV to trigger such activation. Such activation is spatially and temporally unrestricted, that is, can occur both at the PM and on internal membranes discontinuous with the PM, and can continue for prolonged periods of time. Here, we provide the most complete up‐to‐date review of the molecular mechanisms that govern the unique spatiotemporal aspects of non‐canonical G protein activation by GIV and the relevance of this new paradigm in health and disease. Abstract : G protein coupled receptor tyrosine kinase: A unique modular makeup, comprised of a SH2‐like module in tandem with a GEF module allows GIV (red) to bind autophosphorylated cytoplasmic tails of ligand‐activated growth factor receptor tyrosine kinases (RTKs), such as EGFR (green) and to bind and activate Gαi proteins (light blue) by triggering nucleotide exchange (GDP‐to‐GTP). In doing so, GIV facilitates transactivation of G proteins by RTKs.